2022
DOI: 10.3389/fcimb.2022.826603
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Inflammatory Cytokines (IL-6 and IL-18) and Immune Cells in Japanese Encephalitis Patients With Different Progression

Abstract: BackgroundJapanese encephalitis virus (JEV) is the main cause of viral encephalitis in Asia. Nowadays, no effective and specific therapy for JE patients is available except supportive treatment. The fatality rate of JE patients is still about 30%, and more than half of survivors suffered from various neuropsychiatric sequelae. Thus, more attention should be paid to JE.MethodsIn this study, a retrospective cohort of JE patients was collected and the general features of JE patients admitted into the Department o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…IL-18 have been shown to be a diagnostic marker and predictor of inflammatory conditions like myocardial ischemia ( 106 ), acute respiratory distress syndrome ( 107 , 108 ), chronic obstructive pulmonary disease ( 109 ), post infectious bronchiolitis obliterans ( 110 ) and sepsis-induced multi organ injury ( 111 ). IL-18 has also received increase attention in the pathophysiology of neuro-vascular diseases such as in intracerebral hemorrhage ( 112 ), Japanese encephalitis ( 113 ), ocular Behcet disease ( 114 ), abdominal aortic aneurysm ( 115 ), amyotrophic lateral sclerosis ( 116 ), glioma ( 117 ) and most interestingly in cognitive impairment ( 118 ) and agitation in severe mental disease ( 119 ).…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…IL-18 have been shown to be a diagnostic marker and predictor of inflammatory conditions like myocardial ischemia ( 106 ), acute respiratory distress syndrome ( 107 , 108 ), chronic obstructive pulmonary disease ( 109 ), post infectious bronchiolitis obliterans ( 110 ) and sepsis-induced multi organ injury ( 111 ). IL-18 has also received increase attention in the pathophysiology of neuro-vascular diseases such as in intracerebral hemorrhage ( 112 ), Japanese encephalitis ( 113 ), ocular Behcet disease ( 114 ), abdominal aortic aneurysm ( 115 ), amyotrophic lateral sclerosis ( 116 ), glioma ( 117 ) and most interestingly in cognitive impairment ( 118 ) and agitation in severe mental disease ( 119 ).…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…Based on this analysis, we have found that IL6, AKT1, TNF , and PTGS2 exhibited higher interactions and could be considered potential host targets for these natural compounds, as these proteins are also involved in the modulation of key pathways like immune and inflammatory pathways during JE infection. Studies have demonstrated that AKT1, IL6, TNF, and PTGS2 are important players in the immune inflammatory mechanisms associated with JEV infection 43–47 …”
Section: Discussionmentioning
confidence: 99%
“…Based on thisanalysis, we have found that IL6, AKT1, TNF, and PTGS2 exhibited higher interactions and could be considered potential host targets for these natural compounds, as these proteins are also involved in the modulation of key pathways like immune and inflammatory pathways during JE infection. Studies have demonstrated that AKT1, IL6, TNF, and PTGS2 are important players in the immune inflammatory mechanisms associated with JEV infection [43][44][45][46][47]. To predict the mechanism underlying the therapeutic effect of andrographolide, berberine, curcumin, resveratrol, and retinoic acid during JE, we performed GO enrichment analysis of the respective overlapping potential targets of JE and natural compounds.…”
mentioning
confidence: 99%